Students’ Reading Recount Text Mastery - Nurkholila Simatupang; Fitriadi Lubis (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
The aims of the research to describe about students’ ability, difficulties, and the efforts of a teacher in mastery reading of recount text. There were many problems in reading recount text such as the students lack of vocabulary, cannot understand the meaning of the text, lack of motivation, and less of facilities. The research was conducted by mixed research. The researcher used the test and interview to collect the data. After doing the research, it can be concluded that the ability of the grade VIII students of MTsN 3 Tapanuli Selatan in mastering reading recount text based on the test has done, was categorized into “very good” category. The mean score of good category was 85,33. After interviewing the students, the researcher concluded that the students’ problems in mastering reading recount text was in vocabulary mastery, low of understanding the grammar and the generic structure of recount text. While, the efforts have done by the English teacher was keep the students learn, review, and explain detailed about the difficulties that the students got.